Uncommon etiology of a common presentation - Venkatkrishnan, Akila; Chelliah, Suresh; Pachamuthu, Meganathan; Jayabalan, Sathia Dev (International Journal of Contemporary Pediatrics, 2021)
Intussusception is the most common cause of bowel obstruction in infants. The authors present a rare case of intussusception in a SARS-CoV-2 positive infant, and a severity score of 5 on HRCT. This is the first documented case of survival in SARS-CoV-2 patient where intussusception was the primary manifestation, which required surgical intervention.